AVALIAÇÃO DE DESEMPENHO DE ELEMENTOS DE CONTROLE SOLAR MÓVEIS - Domingos, Lucas André Pereira; Cartana, Rafael Prado (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The solar radiation control and the daylight admission can improve the performance of buildings, solar shading devices, when properly applied, can contribute significantly to the comfort and energy efficiency in the built environment, especially if they have a dynamic responsive regarding the climatic variables to which they will be exposed. At the same time, the digital tools have been part of conception process, which improve the production of the contemporary architecture. Based on those considerations this paper aims to evaluate the solar radiation admission, and the luminic performance of movel solar shading devices, developed with parametric modeling. As methodology, initially using the digital suite Rhinoceros3D+Grasshopper a group of and movel (with possibility of movement) solar shading devices were developed, later using the plug-in Diva-for-Rhino were performed solar radiation and daylight performance computational simulations. The main result of this paper is the efficiency of the elements related to its adaptability.